The Influence of Brand Experience on Brand Loyalty Mediated by Perceived Quality and Brand Trust in the Mills Brand - Sunara, Tristano Aviel; Wardhana, Ali (Dinasti Publisher, 2024)
The world has now entered the post-Covid-19 period, we can note that there are changes in socio-cultural aspects that encourage people to make healthy living a trend, one of which is through exercise. This research was conducted through a quantitative approach using data obtained from 170 respondents who bought Mills brand local sports equipment products more than once. The hypothesis testing tool uses the Smart-PLS 3.0 application with the PLS method. This study found that brand experience as an independent variable that has sensory, affective, intellectual and behavioral dimensions along with the mediating variables perceived quality and brand trust simultaneously have a significant influence on the dependent variable brand loyalty. The mediation effect contained in this study is categorized as partial mediation because brand experience also has a significant effect on brand loyalty.